The Considerable Case Reports: Observed Taenia Saginata after Consuming Undercooked Beef - Pegah Golafshan; Seyede Manizhe Heidar Nejadi (Journal of Nutrition and Food Security)
Taeniasis is a significant parasitic infection and zoonotic disease. This study describes the follow-up of a patient with a history of consuming undercooked beef as a result of his occupation. "A 29-year-old, robust and plump individual with a history of working in barbecue preparation", expelled tapeworm of more than 1 meter in length. Initially, by going to a pharmacy, he purchased pyrvinium pamoate suspension", and began treatment (In February 2022, and again in May 2022). Besides, he showed no other gastrointestinal symptoms or complaints except for expelling the entire worm and feeling slightly fatigued. This condition persisted for approximately 1-2 years, during which he regularly consumed raw or undercooked contaminated meat, as well as heart and liver of cattle and calves while preparing barbecue. He elucidated that he had a strong urge to eat them. Unfortunately, his treatment was discontinued when he was imprisoned for three months, during which he did not receive any medication. As a result, he mentioned that he sometimes expelled worms, some of which were more than six meters long. He also described the intense horror he felt when, at times, proglottids (segments of the parasite) appeared in his feces. As far as the author is aware, this is an important report on taeniasis, following years of healthcare efforts against parasitic diseases in Shushtar City, Khuzestan Province